Intelligent Electronics and Circuits Terahertz, ITS, and Beyond - Niu, Mingbo (IntechOpen, 2022)
Intelligent electronics could shape future smart cities and promote initiatives on exploring brand-new integrated circuits, high-effective intelligent reconfigurable surfaces, nondestructive evaluation, terahertz (THz), ITS, 6G, medical and safety imaging, and signal filtering. This book presents mainstream principles, circuitry architectures, and a development roadmap for intelligent electronic systems. Its content ranges from theoretical basis to materials characteristics, and from featured advances to practical applications.